Global Ice Forces and Ship Response to Ice. A Second Season - Minnick, P.; St John, J. (1990)
During September of 1986 the POLAR STAR conducted ice impact tests on ice pressure ridges and ice floes in the Alaskan portion of the Beaufort Sea. Strain gages were used to obtain measurements of the bending strain on the ship hull girder of the POLAR STAR during impacts with ice features. These measurements were then used to calculate the longitudinal bending moment and shear force distributions to arrive at an estimate of the vertical bow force. Compressive strains along the stem and ship acceleration and velocity measurements were also recorded. This report describes the method for determining the global ice impact force from the measurements and presents the results of these tests. Sample hull strain, and impact force time-histories are presented along with the longitudinal bending and shear distributions from several ramming events. Comparison of the results with other available data is presented and the observations are combined with global ice impact loads measured on the POLAR SEA during the previous year. Results indicate that the method used in estimating the impact force contributes to the overall understanding of the ship-ice interaction process.